Natureza e dinâmica de valores na filosofia do espírito livre de Nietzsche - Oscar Augusto Rocha Santos (2011)
The present dissertation aims to discuss the issue of the value dynamics, based on the books covered by the middle period of Nietzsche.s philosophical work, among them the two volumes of Human All Too Human, Daybreak and The Gay Science. Based on an initial effort to characterize the nature of values in a biological-historicist perspective of the issue, we seek to present the gay science as the proper way of life to the free spirit and also advocated by the German philosopher, precisely because of its mode of engagement in the overall change in values.